The Multiomics Analyses of Gut Microbiota, Urine Metabolome and Plasma Proteome Revealed Significant Changes in Allergy Featured with Indole Derivatives of Tryptophan [Corrigendum] - Zhen J; Zhao P; Li Y; Cai Y; Yu W; Wang W; Zhao L; Wang H; Huang G; Xu A (Journal of Asthma and Allergy, 2022)
Zhen J, Zhao P, Li Y, et al. J Asthma Allergy. 2022;15:117—131. The authors have advised there is an error in Figure 2 on page 124. The figure parts B and C have been labelled incorrectly, “B” should read “C” and “C” should read “B”. The authors apologize for this error. Read the original article